NEAR-INFRARED SPECTROSCOPY: A POTENTIAL NEW MEAN OF ASSESSING MULTICOMPONENT POLYHERBAL FORMULATION ON WAY BEFORE AND AFTER EXTRACTION - Maji, Jayanta Kumar (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective:Traditional polyherbal medicine and their preparations have been widely used for the thousands of years in developing and developed countries owing to its natural origin and lesser side effects or dissatisfaction with the results of synthetic drugs. To establish a real time sustainable identification system of polyherbal powder and extract in favor of near infrared-spectroscopy & powder microscopy. To apply the multivariate chemometrics technique PCA, HCA for discrimination both class of multicomponent polyherbal powder and extract by the fundamental attribution of integrity and fuzziness. Â Materials and Method:The authenticated individual herbal, polyherbal pulverized powders & the dry extracts were sifted through eighty meshes. The samples were subjected to NIR spectral detection from 750 to 2500 nm at the interval of 1 nm. The powder microscopy of polyherbal powder, for identification was carried out by following routine procedure. Â Results:Original NIR spectra of polyherbal formulation containing heart-leaved moonseed, Indian Kino, Indian Liac, Ram's horn, Fenugreek, black berry powder and extract showed characteristic hydroxyl hump peaking at about 2200 nm by naked eye. Discrimination of different sample class was also possible through the first order derivative transformation in context relative intensity of NIR sensitive registered generic CH, OH and NH functional group on some wavelength region. The principal component analysis is able to differentiate among samples as a function on PC scores. Conclusion: Chemometric method PCA and HCA is established as a reference library which significantly influences real time quality monitoring of uncontrolled natural variation plant kingdom.Â NIR analysis is useful because a sample may be rapidly tested without destroying its integrity.